2003
DOI: 10.1148/radiol.2293021462
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Regional White Matter Diffusion in Healthy Neonates and Adults Performed with a 3.0-T Head-only MR Imaging Unit

Abstract: There were regional differences in FA and ADC values in the neonates; such variations were less remarkable in the adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
52
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 26 publications
16
52
1
Order By: Relevance
“…However, whereas rodent FA values fall more closely within the range of human infant FA values, ADC values from these rats were lower than in human infants (range: 930 to 1830 × 10 -6 mm 2 /s) (Arzoumanian, et al, 2003;Dubois, et al, 2006;Partridge, et al, 2004;Thomas, et al, 2005). In fact, rodent ADC values for the corpus callosum corresponded better with adult human ADC values (range: 380 to 850 × 10 -6 mm 2 /s) (Huisman, et al, 2006;Lim, et al, 2002a;Zhai, et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, whereas rodent FA values fall more closely within the range of human infant FA values, ADC values from these rats were lower than in human infants (range: 930 to 1830 × 10 -6 mm 2 /s) (Arzoumanian, et al, 2003;Dubois, et al, 2006;Partridge, et al, 2004;Thomas, et al, 2005). In fact, rodent ADC values for the corpus callosum corresponded better with adult human ADC values (range: 380 to 850 × 10 -6 mm 2 /s) (Huisman, et al, 2006;Lim, et al, 2002a;Zhai, et al, 2003).…”
Section: Discussionmentioning
confidence: 86%
“…Sources were parallel planes, 10 pixels lateral to either side of the corpus callosum. The fiber tracking routines developed by Mori and Xu Xu, et al, 2002) and distributed by G. Gerig at University of North Carolina (Zhai, et al, 2003) [www.ia.unc.edu/dev/download/fibertracking] were used and produced pictorial fiber bundle representations. Quantification of the mean FA and ADC of the fibers-"quantitative fiber tracking"-were similar to those we have previously used in vivo in the human brain (Pfefferbaum, et al, 2006b;.…”
Section: Fiber Trackingmentioning
confidence: 99%
“…Single-shot EPI is inherently limited in its through-plane resolution, which could be a potential source of partial volume averaging. [15][16][17] However, the usual through-plane resolution of a clinical EPI for DTI would be approximately 2 Ϯ 0.4 mm, for a FOV of 230 Ϯ 20 mm and phase-encoding steps of 98 -128. Thus, a typical voxel of a clinical DTI examination would be approximately 2 ϫ 2 ϫ 6 mm 3 .…”
mentioning
confidence: 99%
“…It begins in the fetal period and continues into adulthood, but there are also regional differences in the timing of development (Kasprian et al, 2008;Lebel et al, 2012;Zhai, Lin, Wilber, Gerig, & Gilmore, 2003). Research suggests that maturation of fiber tracts during the first 2 years of life in normal developing infants is characterized by three stages 1) rapid change during the first 12 months, 2) slow modifications during the second year, and 3) slower development after 24 months (Geng et al, 2012;Hermoye et al, 2006;Schneider et al, 2004).…”
Section: White Matter Developmentmentioning
confidence: 99%
“…Research suggests that maturation of fiber tracts during the first 2 years of life in normal developing infants is characterized by three stages 1) rapid change during the first 12 months, 2) slow modifications during the second year, and 3) slower development after 24 months (Geng et al, 2012;Hermoye et al, 2006;Schneider et al, 2004). In addition to this characteristic temporal order, fiber tracts develop in region-specific ways (Dubois et al, 2008;Paus et al, 2001;Zhai et al, 2003). Flechsig (1896) showed that white matter development in infants begins first in "projection" pathways of the primary sensory and motor regions.…”
Section: White Matter Developmentmentioning
confidence: 99%